Diterpenoids from the South China Sea soft coral Sarcophyton solidum. (October 2015) - Zhu, Jian-Yong; Li, Wei; Bao, Jing-Mei; Zhang, Jun-Sheng; Yin, Sheng; Tang, Gui-Hua
Abstract: Chemical investigation of the South China Sea soft coral Sarcophyton solidum has led to the isolation of one new (1 ) and seven known (2 –8 ) diterpenoids, including three sarsolenanes (1 –3 ), two capnosanes (4 and5 ), and three cembranes (6 –8 ). Sarsolilide B (4 ) was firstly conﬁrmed by single-crystal X-ray diffraction. Compounds1, 3, 4, and6 –8 were isolated from S . solidum for the first time, and1, 2, and4 –7 were considered as the chemotaxonomic markers for the species S . solidum . Graphical abstract: Highlights: A new sarsolenane-type dierpene was obtained from the South China Sea soft coral Sarcophyton solidum . Seven known diterpenoids including two sarsolenanes, two capnosanes, and three cembranes were reported. Sarsolilide B (4 ) was firstly conﬁrmed by single-crystal X-ray diffraction. Compounds1, 3, 4, and6 –8 were isolated from S . solidum for the first time.